P‐131: Studies on Flickering in Low Frequency Driven Fringe‐Field Switching (FFS) Liquid Crystal Display. Issue 1 (May 2016) - Choi, Han Sol; Kim, Jin Hyun; Ham, Hyeong Gyun; Lim, Young Jin; Lee, Jae Myeong; Jin, Heui Seok; Manda, Ramesh; Kim, Min Su; Yang, Deng-Ke; Lee, Seung Hee
Abstract : Recently, the driving scheme of a fringe‐field switching (FFS) liquid crystal display varies for the best of required performance. Although low‐frequency driving can effectively give rise to reduce power consumption in portable displays, proper controlling of liquid crystal director in direct current is challenging. Particularly, under different polarity of applied electric fields, the transmittance difference along the location of electrodes becomes significant, hence giving rise to an image flickering issue. Here, we investigate how physical properties of a bulk liquid crystalline medium are involved to locally modulate the transmitting light, numerically and experimentally.